Splanchnic Vein Thrombosis: The State-of-the-Art on Anticoagulant Treatment - Custo, Scott; Tabone, Emma; Aquilina, Alexia; Gatt, Alex; Riva, Nicoletta (Hämostaseologie, 2024)
Splanchnic vein thrombosis (SVT) is a rare type of venous thromboembolism occurring within the splanchnic venous system. Portal vein thrombosis is the most common presentation, while Budd–Chiari syndrome is the least common. Liver cirrhosis and abdominal solid cancer are the main local risk factors for SVT, whereas myeloproliferative neoplasms are the predominant systemic risk factors. Signs and symptoms of SVT are nonspecific and include abdominal pain, gastrointestinal bleeding, and ascites. Asymptomatic SVT is not uncommon, and the majority would be detected incidentally on routine abdominal imaging performed for the follow-up of liver diseases and tumors. The management of SVT aims to prevent thrombus progression, promote vessel recanalization, and prevent recurrent venous thromboembolism. Anticoagulation should be started early in order to increase the chances of vessel recanalization and reduce the risk of portal hypertension-related complications. Direct oral anticoagulants have been included in recent guidelines, as alternatives to vitamin K antagonists, after clinical stability has been reached; however, caution is required in patients with liver or kidney dysfunction. Treatment duration is based on the presence (or absence) and type (transient vs. permanent) of risk factors. This narrative review aims to summarize the latest evidence on SVT, with a particular focus on the anticoagulant treatment in special categories of patients (e.g., liver cirrhosis, solid cancer, myeloproliferative neoplasms, pancreatitis, incidentally detected SVT, Budd–Chiari syndrome, and chronic SVT).
Keywords: portal vein thrombosis; splenic vein thrombosis; mesenteric vein thrombosis; Budd-Chiarisyndrome; anticoagulant therapy